2010
DOI: 10.4103/0972-0707.73378
|View full text |Cite
|
Sign up to set email alerts
|

Root canal irrigants

Abstract: Successful root canal therapy relies on the combination of proper instrumentation, irrigation, and obturation of the root canal. Of these three essential steps of root canal therapy, irrigation of the root canal is the most important determinant in the healing of the periapical tissues. The primary endodontic treatment goal must thus be to optimize root canal disinfection and to prevent reinfection. In this review of the literature, various irrigants and the interactions between irrigants are discussed. We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
166
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(178 citation statements)
references
References 89 publications
2
166
0
10
Order By: Relevance
“…Endodontski irigansi imaju važnu ulogu u eliminaciji mikroorganizama iz kanalnog sistema zuba, rastvaranju organskih tkiva, uklanjanju debrisa i razmaznog sloja [1][2][3][4] .…”
Section: Uvodunclassified
See 2 more Smart Citations
“…Endodontski irigansi imaju važnu ulogu u eliminaciji mikroorganizama iz kanalnog sistema zuba, rastvaranju organskih tkiva, uklanjanju debrisa i razmaznog sloja [1][2][3][4] .…”
Section: Uvodunclassified
“…Reakcijom između hlora i amino-grupa formiraju se hloramini koji remete ćelijski metabolizam. Hlor ispoljava antimikrobno dejstvo tako što dovodi do ireverzibilne oksidacije SH grupa esencijalnih bakterijskih enzima 4,7 .…”
Section: Irigansi U Endodoncijiunclassified
See 1 more Smart Citation
“…It is also recommended due to its substantivity, which leads to a longer therapeutic effect. However, Mistry et al (2012) found CHX to be cytotoxic in direct contact with human cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…The best method to clean and shape the root canal remains the subject of considerable debate: Although there are different concepts and strategies for root canal preparation, there is mutual agreement on a chemomechanical preparation that combines a chemical irrigant with a mechanical debridement using hand or rotary instruments [7].…”
Section: Introductionmentioning
confidence: 99%